STIMULATION OF THE DEVELOPMENT OF SMES IN THE NON-OIL SECTOR OF AZERBAIJAN (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The article provides a comprehensive analysis of the directions for stimulating the development of small and medium-sized enterprises (SMEs) in Azerbaijan’s non-oil sector. The author emphasizes that SMEs are a vital driving force of the modern economy, playing a strategic role in economic diversification, employment growth,       regional development, export potential expansion, and the strengthening of innovation activities. By increasing economic flexibility, SMEs also make a significant contribution to improving social welfare and ensuring balanced economic growth. The study notes that as a result of economic reforms and entrepreneurship support measures implemented by the Government of Azerbaijan in recent years, the share of the non-oil sector in GDP has increased significantly compared to 2010, reaching 65–67%. The economic activity, regional influence, and innovative potential of SMEs have also been on the rise. However, several constraints still limit their development. Restricted access to financial resources, high lending interest rates, weak integration into technology and innovation, infrastructure shortcomings, a lack of management skills and human capital, as well as difficulties in accessing international markets, prevent SMEs from fully realizing their potential. The article identifies the main stimulating directions for overcoming these challenges. These include improving state support mechanisms, simplifying tax and administrative procedures, promoting digitalization and innovative initiatives, expanding export missions and international cooperation, and developing infrastructure and human capital, particularly in the regions. In conclusion, the stimulation of SME development is considered a crucial factor for ensuring Azerbaijan’s economic security, sustainable development, and social welfare. Strengthening SMEs will not only reduce the economy’s dependence on oil revenues but also transform the non-oil sector into a key driving force of the national economy.
Keywords: SMEs, non-oil sector, support mechanisms, GDP, stimulation, innovation